PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. INDOMAKMUR SAWIT BERJAYA ROKAN HULU - Ismai, Ismai; aden, Garnasih Lestari; Prima, Andreas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
The research aims to analyze the influence of Occupational Safety and Health (K3) and work motivation on employee work productivity at PT. Indomakmur Sawit Berjaya Rokan Hulu. The population and sample of this research are permanent employees of PT. Indomakmur Sawit Wins in 2022 as many as 89 people. The types of data used in this research are primary data and secondary data. Data collection used in this research is interviews, questionnaires and documentation. The analysis used in this research is descriptive analysis and quantitative analysis. From the research results, it is known that Occupational Safety and Health (K3) variables and work motivation partially influence employee work productivity at PT. Indomakmur Sawit Berjaya Rokan Hulu because the value obtained tcount > ttable. Simultaneously, Occupational Safety and Health (K3) and work motivation have a significant effect on employee work productivity at PT. Indomakmur Sawit was successful in Rokan Hulu because it obtained a value of fcount > ftable. The adjusted R square value was obtained at 0.743, which means that 74.3% of the variable is the amount of employee work productivity at PT. Indomakmur Sawit Berjaya Rokan Hulu can be explained by variations in Occupational Safety and Health (K3)/X1 and work motivation/X2. Meanwhile, the remaining 25.7% is explained by other variables outside those studied. Keywords: Occupational Safety and Health (K3), work motivation and employee work productivity